That is Where God Comes in. Jacob Duym’s Ghedenck-boeck (1606) as Argumentative Discourse - Jansen, Jeroen (My University, 2014)
According to the subtitle, the Ghedenck-boeck (1606) by Jacob Duym learned the reader to forever memorize all evil and malevolence brought about by the Spaniards and their adherents, as well as the great love and fidelity, displayed to the Netherlands by the princes of the Dutch House of Nassau. In this compilation of six stage plays Duym has evoked images from the past, in order to argue that a fair war was better than a fake peace (the title of the last play). They showed the treacherous Spanish enemy as well as the brave-fearless actions of the Dutch, opposing individual Spanish characters to Dutch ones, from the House of Nassau. This paper describes how Duym managed to bring the content of the first five plays as premises into the final play, for instance by applying the technique of moving over from the particular to the general and the other way around. The contribution of God offered an intermediate link, as to see the different individual events in the wider perspective of the common interest and the public welfare of the United Provinces., De acuerdo con el subtítulo, el Libro de la memoria (1606) de Jacob Duym descubre al lector cómo memorizar para siempre toda la maldad causada a los holandeses por los españoles y sus aliados, junto con el amor y fidelidad de los príncipes de la holandesa casa de Nassau. En esta compilación de seis obras de teatro, Duym evoca imágenes del pasado con la intención de argumentar que una guerra justa era mejor que una paz injusta (según el título del último texto). Este conjunto muestra al traidor enemigo español así como las acciones carentes de fiereza de los holandeses, oponiendo personajes españoles y holandeses de la Casa de Nassau. Este artículo describe cómo maneja Duym el contenido de las cinco primeras obras como premisas de la última composición, mediante la técnica de moverse de lo particular a lo general y viceversa. La contribución de Dios ofrece un enlace intermedio para ver los diferentes eventos individuales desde una perspectiva más amplia del común interés y el bienestar público de las Provincias Unidas.
Keywords: Ghedenck-boeck, Rhetoric, Argumentation, Twelve Years Truce, William of Orange, Jacob Duym; Ghedenck-boeck, retórica, argumentación, Tregua de los Doce Años, Guillermo de Orange, Jacob Duym